[Lake Viti at Askja] - Streng, Evelyn Fiedler (1975)
Photograph of Lake Viti at Askja. Brown hills covered in tan and orange rock surround the light blue lake at the bottom of the photograph. A patch of grey sits along the top right edge of the photograph. A steep path sits between two hills at the center of the photograph, a group walking down it.